2017
DOI: 10.1177/1538574417742211
|View full text |Cite
|
Sign up to set email alerts
|

Modern Fixed Imaging Systems Reduce Radiation Exposure to Patients and Providers

Abstract: High-definition fluoroscopic imaging is required to perform endovascular procedures safely and precisely, especially in complex cases, resulting in longer procedures and increased radiation exposure. This is of importance for training institutions as trainees, even with sound instruction in as low as reasonably achievable (ALARA) principles, tend to have high radiation exposures. Recently, there was an upgrade in the imaging system allowing for comparison of radiation exposure to patients and providers. We per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
22
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(23 citation statements)
references
References 28 publications
0
22
1
Order By: Relevance
“…The European Research Journal 2019;5(5):722-728 uclear medicine imaging procedures has been increasingly used over the past 20 years, and theyprovided considerable reductions in morbidity and increases in longevity [1]. 18 Fluorine-fluorodeoxyglucose (18F-FDG) positron emission tomography/ computed tomography (PET/CT) is a molecular imaging technique used to differentiate tumor cells from normal cells. It is especially useful for pre-and post-treatment evaluation of oncology patients [2,3].…”
mentioning
confidence: 99%
See 4 more Smart Citations
“…The European Research Journal 2019;5(5):722-728 uclear medicine imaging procedures has been increasingly used over the past 20 years, and theyprovided considerable reductions in morbidity and increases in longevity [1]. 18 Fluorine-fluorodeoxyglucose (18F-FDG) positron emission tomography/ computed tomography (PET/CT) is a molecular imaging technique used to differentiate tumor cells from normal cells. It is especially useful for pre-and post-treatment evaluation of oncology patients [2,3].…”
mentioning
confidence: 99%
“…PET/CT has proven useful in management of several tumors. Since urinary excretion of 18 F-FDG radiotracer masks the presence of lesions, diagnostic power of PET/CT scanning is lower in urologic tract tumors and prostate cancer [6]. It was reported that PET/CT scanning has a high frequency of false-negatives in urologic tumors [7].…”
mentioning
confidence: 99%
See 3 more Smart Citations